Elucidation of target implant orientations with the safety range of hip rotation with adduction or abduction during squatting: Simulation based on in vivo replaced hip kinematics - Harada, Satoru; Hamai, Satoshi; Ikebe, Satoru; Hara, Daisuke; Higaki, Hidehiko; Gondo, Hirotaka; Kawahara, Shinya; Shiomoto, Kyohei; Harada, Tetsunari; Nakashima, Yasuharu (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: The study aimed to elucidate target cup orientation and stem anteversions to avoid impingement between the liner and stem neck even at hip rotation with adduction during the deeply flexed posture. Methods: A computer simulation analysis was performed on 32 total hip arthroplasty patients applying patient-specific orientation of the components and in vivo hip kinematics obtained from three-dimensional analysis of the squatting motion. The anterior/posterior liner-to-neck distance and impingement were evaluated based on a virtual change in internal/external rotation (0°–60°) and adduction/abduction (0°–20°) at actual maximum flexion/extension during squatting. Cutoff values of cup orientations, stem anteversion, and combined anteversion to avoid liner-to-neck impingements were determined. Results: The anterior liner-to-neck distance decreased as internal rotation or adduction increased, and the posterior liner-to-neck distance decreased as external rotation or adduction increased. Negative correlations were found between anterior/posterior liner-to-neck distances at maximum flexion/extension and internal/external rotation. Anterior/posterior liner-to-neck impingements were observed in 6/18 hips (18/56%) at 45° internal/external rotation with 20° adduction. The range of target cup anteversion, stem anteversion, and combined anteversion to avoid both anterior and posterior liner-to-neck impingements during squatting were 15°–18°, 19°–34°, and 41°–56°, respectively. Conclusion: Simulated hip rotations caused prosthetic impingement during squatting. Surgeons could gain valuable insights into target cup orientations and stem anteversion based on postoperative simulations during the deeply flexed posture.